THE STATUS AND MANAGEMENT OF MOOSE IN THE MURMANSK REGION, RUSSIA - Makarova, Olga A; Khokhlov, Anatoly M (Lakehead University, 2009)
The moose population in the Murmansk region has changed considerably in the past century. Moose appeared in the forest-tundra zones in the 1950s, occupied the Ponoy River area in the 1960-1970s, and population growth occurred to the north of the forest zone along the tributaries and rivers flowing into the Barents Sea. Some wintered in open tundra, but more commonly moose migrated between tundra and forested winter habitat. Official harvests began in the 1950s and were managed by Murmanskiy, a state owned company. A 5-year harvest ban was initiated in 1982 to recover the population; however, current harvest remains about a third of previous levels and the proportional harvest of calves and yearlings is higher. The current population is in good condition based upon weight and productivity data, occupies suitable winter habitat, and is not impacted by severe winter conditions. Because the Murmansk region is at the northern extent of moose range, management should focus upon regulated harvests, adequate population surveys, seasonal habitats and migratory corridors, the impact of harvest quotas and poaching, and the possible influence of global warming.